Small mammal use of native warm‐season and non‐native cool‐season grass forage fields - Ryan L. Klimstra; Christopher E. Moorman; Sarah J. Converse; J. Andrew Royle; Craig A. Harper (Wildlife Society Bulletin)
ABSTRACT Recent emphasis has been put on establishing native warm‐season grasses for forage production because it is thought native warm‐season grasses provide higher quality wildlife habitat than do non‐native cool‐season grasses. However, it is not clear whether native warm‐season grass fields provide better resources for small mammals than currently are available in non‐native cool‐season grass forage production fields. We developed a hierarchical spatially explicit capture–recapture model to compare abundance of hispid cotton rats (Sigmodon hispidus), white‐footed mice (Peromyscus leucopus), and house mice (Mus musculus) among 4 hayed non‐native cool‐season grass fields, 4 hayed native warm‐season grass fields, and 4 native warm‐season grass–forb (“wildlife”) fields managed for wildlife during 2 summer trapping periods in 2009 and 2010 of the western piedmont of North Carolina, USA. Cotton rat abundance estimates were greater in wildlife fields than in native warm‐season grass and non‐native cool‐season grass fields and greater in native warm‐season grass fields than in non‐native cool‐season grass fields. Abundances of white‐footed mouse and house mouse populations were lower in wildlife fields than in native warm‐season grass and non‐native cool‐season grass fields, but the abundances were not different between the native warm‐season grass and non‐native cool‐season grass fields. Lack of cover following haying in non‐native cool‐season grass and native warm‐season grass fields likely was the key factor limiting small mammal abundance, especially cotton rats, in forage fields. Retention of vegetation structure in managed forage production systems, either by alternately resting cool‐season and warm‐season grass forage fields or by leaving unharvested field borders, should provide refugia for small mammals during haying events. © 2014 The Wildlife Society.